Penegakan Hukum, Penyidikan, Pen Penegakan Hukum Pada Penyidikan Terhadap Tindak Pidana Pencemaran Nama Baik Yang Dilakukan Di Media Sosial (Studi Kasus Kepolisian Resor Kerinci): Penegakan Hukum Pada Penyidikan Terhadap Tindak Pidana Pencemaran Nama Baik Yang Dilakukan Di Media Sosial (Studi Kasus Kepolisian Resor Kerinci) - Yetti, Hafiza; Ismansyah, Ismansyah; Mulyati, Nani (Lareh Law Review, 2025)
Defamation through social media is included in information crimes and Electronic Transactions regulated in the Criminal Code and Law Number 11 of 2008 concerning Information and Electronic Transactions as last amended by Law Number 1 of 2024 concerning Information and Electronic Transactions used to protect victims of defamation, The problems in this thesis are: 1) How is the interpretation of defamation committed on social media in criminal law? 2) How is the enforcement of criminal law against perpetrators of criminal acts of defamation through social media in Sungai Penuh City? 3) What are the obstacles and efforts in enforcing the law against criminal acts of defamation committed on social media in Sungai Penuh City? This study uses an empirical legal method, is descriptive in nature using primary data obtained from interviews with investigators and the research location at the Kerinci Police Resort. The results of the study show that: 1) The interpretation of defamation in the Criminal Code that is still in effect, the New Criminal Code, the Old ITE Law, the New ITE Law, and the Constitutional Court Decision No. 78/PUU-XXI/2023. The provisions of the Criminal Code that are still in force are more general, while the New Criminal Code and the New ITE Law more clearly regulate defamation. The Constitutional Court's decision also provides legal certainty. 2)Iinvestigation stage of reports received from 2022-2024 there were 13 cases and 4 cases that were processed were resolved through mediation. 3) Obstacles faced by Kerinci Police investigators in enforcing the law on criminal acts of defamation through social media are problems with evidence, limited technical expertise in the field of digital forensics, lack of legal awareness among the public, limited budget and resources, cultural and social differences in society. Keywords : Defamation, Investigation, Law Enforcement, Social Media